2019
DOI: 10.1186/s11658-019-0191-8
|View full text |Cite
|
Sign up to set email alerts
|

Cellular hypoxia promotes osteogenic differentiation of mesenchymal stem cells and bone defect healing via STAT3 signaling

Abstract: BackgroundHypoxia in the vicinity of bone defects triggers the osteogenic differentiation of precursor cells and promotes healing. The activation of STAT3 signaling in mesenchymal stem cells (MSCs) has similarly been reported to mediate bone regeneration. However, the interaction between hypoxia and STAT3 signaling in the osteogenic differentiation of precursor cells during bone defect healing is still unknown.MethodsIn this study, we assessed the impact of different durations of CoCl2-induced cellular hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 41 publications
1
35
2
3
Order By: Relevance
“…In MSC, the peak of VEGF expression occurs after 3 days of hypoxia. Hypoxia also enhanced expression and phosphorylation of STAT3 and inhibiting STAT3 reversed the VEGF induction [ 52 ]. Signal transducer and activator of transcription 3 signaling is important and necessary for endothelial cell proliferation, migration, and microvascular tube formation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MSC, the peak of VEGF expression occurs after 3 days of hypoxia. Hypoxia also enhanced expression and phosphorylation of STAT3 and inhibiting STAT3 reversed the VEGF induction [ 52 ]. Signal transducer and activator of transcription 3 signaling is important and necessary for endothelial cell proliferation, migration, and microvascular tube formation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic mice, specific inactivation of STAT3 in osteoblasts and osteocytes decreased mechanical load-driven bone formation [ 55 ]. CoCl 2 , a mimic of hypoxia, enhanced migration in MSCs and promoted osteogenic differentiation of MSCs and bone defect healing via STAT3 phosphorylation upregulation [ 28 , 52 ]. An increase in STAT3 phosphorylation was also observed during differentiation of human osteoprogenitors.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, both MSCs and the media from bone marrow-derived MSCs cultured under hypoxic conditions demonstrated increased amounts of basic fibroblast growth factor (bFGF), vascular endothelial growth factor A (VEGF-A), interleukin 6 (IL-6), and interleukin 8 (IL-8), and enhanced the proliferation and migration of endothelial cells and other cells including macrophages (Chen et al, 2014 ). Osteogenesis and angiogenesis are also controlled by the transcription factor Signal Transducer and Activator of Transcription 3 (STAT3), an important regulator of bone homeostasis (Yu et al, 2019 ). Using murine MSCs in vitro and a femoral defect model, hypoxia was shown to upregulate the phosphorylation of STAT and was important to the healing of a bone defect.…”
Section: Methods To Enhance the Function Of Harvested Cells ( mentioning
confidence: 99%
“…Using murine MSCs in vitro and a femoral defect model, hypoxia was shown to upregulate the phosphorylation of STAT and was important to the healing of a bone defect. Interestingly, the duration of hypoxia was critical to osteogenesis and angiogenesis, with 3 days of exposure being optimal (Yu et al, 2019 ). Other studies in animals have confirmed hypoxic preconditioning as a method to enhance osteogenesis, angiogenesis and bone healing, even in aged animals (Fan et al, 2015 ; Zhang et al, 2018 ).…”
Section: Methods To Enhance the Function Of Harvested Cells ( mentioning
confidence: 99%
“…Odontogenesis was determined by cellular accumulation of alizarin red-stained mineralized matrix. The mineralized matrix in different culture conditions was quantified as described previously (Yu et al, 2019).…”
Section: In Vitro Matrix Mineralization Assaymentioning
confidence: 99%